Fauna of sandy beaches in Bachok, Kelantan - Sasekumar, A.; Moh, H.H.; Muhammad Ali, S.H. (Faculty of Science, University of Malaya, 2010)
The fauna of two sandy beaches on the Bachok coast of Kelantan were studied during June 2008. Sand was dug up to a depth of 30 cm with a spade, and washed in a sieve of 2 mm-mesh size at the water's edge to collect the fauna. Fifteen species of invertebrates consisting of gastropods, bivalves, crustaceans and an echinoderm were recorded. The most common were ghost crab Ocypode ceratophthalma, sand bubble crab Scopimera proxima, hermit crab Diogenes avarus, bivalve Meretrix sp. and sand dollar Arachnoides placenta. The moist sand in the lower part of the shore supported a higher diversity of fauna than the dry sand of the upper shore.